THE IMPACT ON LEARNING OF AN ASYNCHRONOUS ACTIVE LEARNING COURSE FORMAT - Spiceland, David; Hawkins, Charlene P. (Online Learning, 2002)
Among the many differences between asynchronous interactions and traditional classroom communication, the most critical differences involve those that may affect a student’s ability to learn. The efficacy of courses in facilitating instruction and learning is a key concern of all educators involved in or contemplating conducting such courses. This paper explores the impact on learning in asynchronous internet courses compared to learning in a traditional classroom setting. Specifically, the study examines student perceptions of the effectiveness of an active-learning, asynchronous internet course relative to that of a traditional classroom-based course. Students were asked to compare effectiveness on a variety of dimensions. The study yields results consistent with previous research related to learning outcomes along several measures, particularly with regard to students’ positive attitudes about their learning in an online computer course. However, the findings here offer new evidence that learning can also be enhanced with an active learning format in an online course.